Pemberdayaan Kewirausahaan pada Kelompok Himpunan Wanita Penyandang Disabilitas Kota Bengkulu - Benardin; Yusnida Yusnida; Aris Almahmudi (Kreativasi : Journal of Community Empowerment, 2023)
The business activities of groups of people with disabilities in the city of Bengkulu face various problems and obstacles, including the low quality of human resources and entrepreneurial abilities of people with disabilities, limited capital, marketing networks, limited use of IT media in promotion and marketing, so that the development of businesses with disabilities does not progress significantly. significant. The aim of this community service activity is to increase the entrepreneurial knowledge of people with disabilities who are members of the Bengkulu city branch of the Indonesian Women with Disabilities Association (HWDI). The benefits of this empowerment activity include increasing the entrepreneurial knowledge of people with disabilities who are members of the Bengkulu city branch of the Indonesian Women with Disabilities Association (HWDI).